Urban Integration - Mia Dorćol, Belgrade - Gnjato, Milka (Arhitektura i urbanizam, 2021)
The effort to recreate the continuity of values in the existing context, both in terms of architecture and always inextricably linked to it and in the cultural sense, is realized through honesty. Honesty actually means achieving a relationship between the functional and tectonic system of the object itself and its appearance through an understanding of the spatial-semantic multidimensionality of the context. The semantic, dialogical and dualistic principles of contextualization, which ultimately has the true three-dimensionality of the facade itself, and which arose from the system and function of the building, established the identity and value continuity of architectural heritage, created during the industrialization of Belgrade and Serbia.
Keywords: urban integration; contextual architecture; contemporary interpretation of the architectural heritage of industrial buildings